Dari Eden ke Era Postmodern: Reinterpretasi Pohon Pengetahuan Dalam Kejadian 3 Di Tengah Krisis Otoritas Digital - Sembel, Injilia Belani (Sekolah Tinggi Teologi Kharisma, 2025)
Basically, the knowledge that each individual has can reflect the quality and identity of the person himself. For Christians, the main knowledge that is the basis of a life of faith is sourced from the word of God in the Bible. This study examines the meaning of the Tree of Knowledge in Genesis 3 with a three-step approach: (1) looking at the historical context of King Solomon's time, (2) analyzing the text itself, and (3) relating it to modern issues (Tate, 2008). The results show that this story is not just a story of sin, but also illustrates the struggle against the mastery of knowledge - as we see today in the dominance of digital technology (Campbell, 2020). The study found three important things: first, the prohibition of eating the fruit reflects the danger of monopolizing knowledge; second, the desire “to be like God” is similar to modern technological (transhumanistic) ambitions; third, the story teaches the importance of wisdom in using technology. The study concludes that the story of the Tree of Knowledge is relevant to help us face challenges in the digital age.